2002
DOI: 10.1074/jbc.m109661200
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Activity-modifying Protein 1 Determines the Species Selectivity of Non-peptide CGRP Receptor Antagonists

Abstract: . This observation provided an opportunity to map the determinants of receptor affinity exhibited by BIBN4096BS and the truncated analogs, Compounds 1 and 2. All three compounds exhibited higher affinity for the human receptor, human CRLR/human RAMP1, than for the rat receptor, rat CRLR/rat RAMP1. We have now demonstrated that this species selectivity was directed exclusively by RAMP1. By generating recombinant human/rat CRLR/RAMP1 receptors, we demonstrated that co-expression of human CRLR with rat RAMP1 prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
154
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(163 citation statements)
references
References 21 publications
7
154
0
Order By: Relevance
“…Transfections were performed by combining 60 µg/dish DNA with 180 µg/dish Lipofectamine 2000 (Invitrogen, Carlsbad, CA). Rat CLR and RAMP1 cDNAs in the mammalian expression construct pcDNA3.1, described earlier (Mallee et al, 2002), were co-transfected in equal amounts. Transfection cocktail was added directly to the medium and the cells were harvested for membranes 48 h post-transfection.…”
Section: Cell Culture and Generation Of Recombinant Cell Linesmentioning
confidence: 99%
“…Transfections were performed by combining 60 µg/dish DNA with 180 µg/dish Lipofectamine 2000 (Invitrogen, Carlsbad, CA). Rat CLR and RAMP1 cDNAs in the mammalian expression construct pcDNA3.1, described earlier (Mallee et al, 2002), were co-transfected in equal amounts. Transfection cocktail was added directly to the medium and the cells were harvested for membranes 48 h post-transfection.…”
Section: Cell Culture and Generation Of Recombinant Cell Linesmentioning
confidence: 99%
“…In rats, no changes in heart rate, mean arterial pressure, systemic vascular conductance, or cardiac output were observed with BIBN4096BS at 3 mg/kg (Arulmani et al, 2004). Compared with rat CGRP receptors, human CGRP receptors have Ͼ100-fold the affinity for BIBN4096BS (Mallee et al, 2002). In the first clinical trial published by Olesen et al (2004), the maximum response rate after 2 h of drug administration occurred at a dose of ϳ70 g/kg.…”
Section: Doses Of Bibn4096bs In Comparison With Other Studiesmentioning
confidence: 99%
“…According to the authors, no intrinsic cardiovascular effects were reported. The affinity of olcegepant for the CGRP receptor was RAMP1 related, directly competing with CGRP for its binding site [73]. In 2004, Olesen et al [74] reported the positive outcomes of CGRP-RA as a migraine-abortive therapy with similar effectiveness to that of oral sumatriptan.…”
Section: Cgrp Receptor Antagonistsmentioning
confidence: 99%